Dual blockade of the lipid kinase PIP4Ks and mitotic pathways leads to cancer-selective lethality - Mayumi Kitagawa (Nature Portfolio, 2017)
The Ras/Raf/MEK/ERK and PI3K/Akt/mTOR signaling pathways are essential for cancer cell survival. Here, the authors describes a molecule a131 with dual-inhibitory properties, which targets PI5P4K and mitosis, and it is involved in Ras/Raf/MEK/ERK and PI3K/Akt/mTOR crosstalk, thereby causing reversible growth arrest in normal cells and cell death of tumor cells.